Leading small and mid-sized urban school districts - Sutherland, Ian E.; Sanzo, Karen; Scribner, Jay Paredes, 1963- (Advances in educational administration,, 2015)
The majority of the research in the US public education system has been conducted in large urban areas that do not reflect the majority of urban systems. The categorization of the size of districts does not capture the organizational diversity and complexity of school systems, including at-risk students and other demographic variables. The implications are that policy, preparation, research and funding are adversely skewed by an overrepresentation of research in urban districts that do not reflect the majority. This edited collection explores the ways in which small to mid-sized school districts influence leadership preparation, leadership practice, and accountability and assessment. With contributions from respected specialists, the volume addresses topics such as coaching, poverty, leadership preparation programs, accountability and assessment, English Language Learners, district leadership, and organizational learning and trust.